International trade and informality - Demirci, Özge. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
In this thesis, we empirically and theoretically investigate whether the presence of an informal sector contributes positively to exports of an economy. Using annual bilateral trade data of 161 economies over the period from 1960 to 2009, we run several estimations and find that a relatively larger informal sector in the exporting economy is associated with a higher amount of exports to the importing country. In line with this empirical result, we also construct a Melitz-type model of trade incorporating informal sector to examine different channels through which informality might affect trade. The model also sheds light on several policy changes with respect to the informal sector as well as international trade.
Keywords: Informal sector (Economics)